2007
DOI: 10.1097/00054725-200705005-00012
|View full text |Cite
|
Sign up to set email alerts
|

Novel targets identified in gene expression profiles from patients with inflammatory bowel disease

Abstract: a non discriminative way and thus selected the un-expressed cII gene in LIZ transgenes of Big Blue ™ (BB) mice to study. Because the available BB mice were on B6 genetic background, which has profound effect on tumor susceptibility, we generated B6 BB Gpx1/2-DKO mice and studied their phenotype. The B6 BB Gpx1/2-DKO mice had fewer inflammatory cells, milder ileocolitis, low mortality before 7 weeks of age, and only 2.5% of them developed tumors between 6-8 months old. Whether these Gpx1/2-DKO mice have LIZ tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The authors showed that in CD, 4 analytes (PLGF, IL-7, IL-12p40, and TGF-beta1) were significantly elevated in patients in clinical remissions when compared to those with active disease, while in UC only 1 cytokine (IL12p40) showed significance between clinical remissions and active disease. This study (32) suggests that these cytokines are directly involved intestinal inflammation in IBD, and is in agreement with our data obtained by multiplex ELISA (33, 34). …”
Section: Proteomic Approachessupporting
confidence: 92%
See 3 more Smart Citations
“…The authors showed that in CD, 4 analytes (PLGF, IL-7, IL-12p40, and TGF-beta1) were significantly elevated in patients in clinical remissions when compared to those with active disease, while in UC only 1 cytokine (IL12p40) showed significance between clinical remissions and active disease. This study (32) suggests that these cytokines are directly involved intestinal inflammation in IBD, and is in agreement with our data obtained by multiplex ELISA (33, 34). …”
Section: Proteomic Approachessupporting
confidence: 92%
“…It is necessary to point out that another powerful protein/antibody-based technology, multiplex ELISA, was not included in this review. Recently multiplex ELISA has been proven as a robust approach to profile biomarkers of various diseases, and we have demonstrated its potential in profiling and identifying serum cytokines/chemokines as serological IBD biomarkers (32, 33). It’s evident that the proteomic study of IBD is in a very early stage, when compared to its application in other diseases (such as cancer).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations